The Diversity of Arthropods Predator on Wild Plant of Rice Field with and without Pesticides - Meidalima, Dewi; Kawaty, Ruarita Ramadhalina; Gunawan, Erlan B. (Biosaintifika: Journal of Biology & Biology Education, 2017)
Contaminated- agro ecosystem influences abundance and diversity of arthropods. The aims of this study were to analyze the diversity and abundance of pre-planting arthropod predators on wild plants in rice field with and without application of pesticides. The survey and direct observation of wild plants at the rice filed were conducted from January to March 2015, at 1 ha in Pemulutan and 1 ha in Musi 2 Palembang. Sampling of arthropod predator was conducted 8 times before the rice was grown, using insect nets. On the land without pesticide application was found 14 arthropod families which consists of 28 species and 15 families of wild plant consists of 25 species. On the land with pesticide application was found 8 arthropod families consists of 16 species and 15 wild plant families with 23 species. On the land without pesticide application was found High index of diversity (H=3.121) and low dominance (D=0.095), while on the land with pesticide application low index of diversity (H=2.602) and high dominance (D=0.171). It is the indicators of arthropods predator more varieties at the land without pesticide application compare to the land with pesticide application. This finding is very important for biological pest management in South Sumatra.